Field Observation-Based Inventory Audit Assistance for MSME Aura Parfum to Improve Inventory Information Accuracy and Internal Control Quality - Wahyuni; Reni Handayani.S; Nirwhana Yuliana Ahmad; Syahra Darajat Salsabila; Fakhirah Naila Zalianty (Masterpiece, 2026)
Inventory management is a crucial aspect of maintaining operational smoothness and enhancing internal control quality for Micro, Small, and Medium Enterprises (MSMEs). However, many MSMEs still face challenges in inventory recording, resulting in information that is not entirely accurate. This Community Service activity aimed to provide guidance on a field-observation-based inventory audit for Aura Parfum to evaluate the accuracy of inventory information and the quality of internal controls. The methods employed included internal control interviews, physical warehouse observation using a checklist, and a physical stock count (stock opname) of fourteen perfume essence samples. Data were analyzed descriptively to identify the alignment between inventory records and actual physical conditions. The results indicated that Aura Parfum had effectively implemented physical inventory controls through the segregation of storage areas, raw material labeling, temperature control, and restricted warehouse access. Nevertheless, the inventory recording system remained manual and periodic, leading to discrepancies found in three types of perfume essences during the physical stock count. These findings suggest that the discrepancies were caused more by delays in recording than by actual inventory loss. The activity resulted in recommendations to implement a perpetual inventory recording system, conduct regular physical stock counts, separate the recording of online and offline sales transactions, and establish a mechanism for monitoring supplier payments. Implementing these recommendations is expected to improve inventory information accuracy and strengthen the MSME's internal control system.